IDENTIFIKASI JENIS DAN PEMANFAATAN TUMBUHAN OBAT DI HUTAN TEMBAWANG OLEH MASYARAKAT KELURAHAN BERINGIN KECAMATAN KAPUAS KABUPATEN SANGGAU - Rahman, Khairul; Wardenaar, Evy; Mariani, Yeni (JURNAL HUTAN LESTARI, 2019)
AbstractThis research was carried out in four locations of the Tembawang Forest in Lingkungan Semajau Â (RW 9), namely Semajau (T1), Tebanan (T2), Sebayur (T3), and Koling (T4). In addition, interviews were also held with people who living near health facilitiy (RW 2), in Beringin Village of Kapuas Subdistrict of Sanggau Regency, West Kalimantan. This research aims to documented the medicinal plants and the knowledge of medicinal plants utilization used by traditional healers and communities of RW 2 and RW 9 of Beringin Village. In this research, we found a total of number of 100 medicinal plants species used by traditional healers, and it belonging into 55 families. The most common family is the Zingiberaceae, and tree habitus is the most common habitus found in all four Semajau tembawang forests. The parts of medicinal plants used by the community of Beringin Village are in the form of roots, seeds, fruit, flowers, leaves, bark, fruit skin, rhizomes, tubers, and all parts of medicinal plants. The most common method of processing medicinal plants is boiling, and oral (eat or drink) are the most common administration method.Keywords: Beringin Village, Medicinal Plants, Sanggau Regency, Tembawang Forest, Traditional Knowledge.